Efektivitas Penggunaan Model Quantum Teaching dalam Meningkatkan Hasil Belajar IPA - Wote, Alice Yeni Verawati; Sasingan, Mardince; Kitong, Okvin Elserlis (Journal of Education Technology, 2020)
The aim of this research was to determine the significant difference in the application of quantum teaching learning model in natural science subject. This research was conducted on fourth grade students of SD INPRES Kupa-Kupa with the population of 20 students. The sample of this research divided into control group consisted of 10 students and the experimental group consisted of 10 students. This research used a post-test only design. Data analysis used normality, homogeneity and hypothesis test. The result showed that the average score obtained by post test of experimental group, it was 87 higher than control group, it was 52. The t-count = 14.42 > t-table = 2.228, it could be concluded that H0 was rejected and ð»ð‘Ž was accepted or the application of a quantum teaching learning model could improve the learning outcomes on fourth grade elementary students